Association between serum estradiol levels and cognitive function in older women: a cross-sectional analysis - Xu, Qian; Ji, Meng; Huang, Shicai; Guo, Weifeng (Frontiers in Aging Neuroscience, 2024)
Estradiol is a sex steroid hormone,which has been implicated in the pathogenesis of Alzheimer's disease and cognitive impairment. This cross-sectional study aimed to examine the relationship between serum estradiol levels and cognitive performance in older American women.: Data were obtained from the National Health and Nutrition Examination Survey 2013-2014. A total of 731 women aged ≥60 years who met the inclusion criteria were included in this study.Serum estradiol levels were measured using the isotope dilution liquid chromatography tandem mass spectrometry (ID-LC-MS/MS) method developed by the Centers for Disease Control and Prevention for routine analysis. All measured serum levels were further divided into three parts: T1, <3.68 pg/mL; T2, 3.68-7.49 pg/mL; T3, >7.49 pg/mL, and analyzed. Participants' cognitive abilities were tested using the Vocabulary Learning Subtest (CERAD), Animal Fluency Test (AFS), and digital symbol substitution test (DSST). Scores for each test were calculated based on the sample mean and standard deviation (SD). To examine the relationship between serum estradiol level tertiles and cognitive scores, multiple linear regression models were developed, controlling for race/ethnicity, education level, hypertension, diabetes, and insomnia. Results：The mean age of the participants was 69.57 ± 6.68 years. The non-Hispanic whites were 78.95%, and those who had completed at least some college-level education were 60.62%. The mean BMI of the participants was 29.30 ± 6.79, and 10.85% had a history of smoking. Further, 73.41% did not have a history of alcohol consumption, and 63.03% had hypertension (63.03%). In addition, 81.81% and 88.3% did not have a history of diabetes mellitus and did not have sleep disorders, respectively. The mean serum estradiol level was 8.48 ± 0.77 pg/mL. Multivariate linear regression of the reference group consisting of participants in tertiles of serum estradiol levels revealed that one unit increase in serum estradiol levels increased DSST scores by 0.61 (0.87, 6.34) in the T3 group. However, no significant correlation was found in the CERAD and AFS tests. Conclusion: Participants with higher estradiol levels had higher DSST scores and better processing speed, sustained attention, and working memory, suggesting that serum estradiol may serve as a biomarker for cognitive decline in older women.